2023
DOI: 10.3390/cancers15020511
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Ion-Responsive lncRNA EBLN3P Functions in the Radiosensitization of Non-Small Cell Lung Cancer Cells Mediated by TNPO1

Abstract: In recent decades, the rapid development of radiotherapy has dramatically increased the cure rate of malignant tumors. Heavy-ion radiotherapy, which is characterized by the “Bragg Peak” because of its excellent physical properties, induces extensive unrepairable DNA damage in tumor tissues, while normal tissues in the path of ion beams suffer less damage. However, there are few prognostic molecular biomarkers that can be used to assess the efficacy of heavy ion radiotherapy. In this study, we focus on non-smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It has been demonstrated that lncRNA EBLN3P has crucial functions in various cancers, including liver cancer [32], osteosarcoma [14], CRC [13] and lung cancer [33]. EBLN3P silencing suppressed liver cancer cell proliferation, migration, and invasion, while lncRNA EBLN3P overproduction stimulated these cellular progresses [32].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that lncRNA EBLN3P has crucial functions in various cancers, including liver cancer [32], osteosarcoma [14], CRC [13] and lung cancer [33]. EBLN3P silencing suppressed liver cancer cell proliferation, migration, and invasion, while lncRNA EBLN3P overproduction stimulated these cellular progresses [32].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that LNC EBLN3P can promote the progression of osteosarcoma and rectal cancer by regulating different ceRNA axes, and can lead to the resistance of osteosarcoma cells to methotrexate [ 24 , 25 , 26 ]. The downregulation of LNC EBLN3P using various methods (such as siRNA, shRNA silencing pathway, or carbon ion beam irradiation) can enhance the therapeutic effect by inhibiting malignant behavior of tumor cells, inducing apoptosis of tumor cells, and increasing radiation sensitivity [ 9 , 27 , 28 ]. Therefore, LNC EBLN3P is a carcinogenic factor and therapeutic target for tumors.…”
Section: Discussionmentioning
confidence: 99%
“…LNC EBLN3P has emerged as a focal point of interest, given its dysregulation in diverse malignancies such as osteosarcoma, liver cancer, and breast cancer [ 24 , 60 , 61 ]. Furthermore, in a previous study by our team, the expression of LNC EBLN3P in lung cancer cell lines was much higher than in the normal lung bronchial epithelial cell line BEAS-2B, indicating its potential as a therapeutic target in NSCLC [ 9 ]. Nevertheless, the precise targeting and inhibition strategies for LNC EBLN3P in the context of tumor eradication remain an uncharted territory, thus signifying an imperative avenue for our forthcoming investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation